Association Rule Mining with IST-EFP Algorithm The Novelty of FP-Growth Algorithm - Boby Siswanto; The Liong; Shaufiah Shaufiah (eProceedings of Engineering, 2014)
EFP algorithm is an FP-Growth algorithm that is applied to the DBMS such as Oracle DBMS. IST-EFP algorithm is the improvement of EFP algorithm which is combined by intersection of set theory analysis. IST-EFP algorithm will reduce items from the original dataset that have low support value. ISTEFP algorithm has better performance than EFP algorithm because it reduces more items while maintaining the confidence values of the association rules obtained. Keywords—EFP algorithm; IST-EFP algorithm; Oracle DBMS; item reductions; maintain confidence values; association rules.